Charitable giving law made easy - Hopkins, Bruce R. (Wiley & Sons, 2007)
This authoritative guide presents in-depth discussions on such hot topics as the timing of charitable deductions, estate and gift tax considerations, special property rules, and planned giving. Packed with practical tips and hard-to-find advice, Charitable Giving Law Made Easy sheds light on complex legal issues concerning charitable giving with plain-language explanations of laws and regulations for non-legal professionals.